Millet and meals: the role and significance of Panicum miliaceum in culinary contexts at Bruszczewo, Poland - Standall, Edward A.; Craig, Oliver E.; Kneisel, Jutta; Müller, Johannes; Kirleis, Wiebke; Czebreszuk, Janusz; Heron, Carl (Archaeological and anthropological sciences, 2025)
The translocation of broomcorn millet ( Panicum miliaceum ) is an enticing subject of archaeological investigation. While the species was rapidly dispersed across Eurasia during prehistory, its adoption appears to have been inconsistent, with evidence for its sudden and gradual adoption, as well as its rejection, observed within and between contemporary communities and cultures. The translocation of P. miliaceum may be better understood through the identification of its role and significance as a foodstuff among past populations. This study employs molecular investigation and bulk and compound-specific isotope analysis to study organic residues produced during culinary activities at Bruszczewo, Poland, during the Early Bronze Age (EBA) and Late Bronze Age / Early Iron Age (LBA/EIA). The analysis of ceramic-absorbed and charred ‘foodcrust’ residues enabled a comprehensive examination of vessel use-life and the production of individual meals. This study strongly suggests that P. miliaceum was not present at Bruszczewo during the EBA, conforming to its established translocation chronology, while highlighting its extensive use during the LBA/EIA. The cereal was incorporated into a variety of culinary activities, constituting both a minor and major ingredient of many meals, while being absent in others. Finally, the observation of apparently unrestricted use of P. miliaceum at Bruszczewo provided further insight into the role and significance of this cereal relative to contemporary LBA/EIA evidence for its use across the region.